OT-Parentship Effectiveness on Parental Resilience, Self-Determination, and Occupational Performance of Parents and Their Autistic Adolescents: Pragmatic Randomized Controlled Trial. - Wachspress, Batel; Maeir, Adina; Tsafrir, Shlomit; Mazor-Karsenty, Tal (American Journal of Occupational Therapy)
Importance: Parents of autistic adolescents often experience unique caregiving responsibilities and significant stress, leading to challenges in navigating the complexities of their role and affecting their quality of life. Enhancing parental resilience is crucial for supporting autistic adolescents' needs and fostering positive family outcomes. Objective: To investigate the effectiveness of the OT-Parentship intervention in enhancing parental resilience, self-determination, and occupational performance of parents and their autistic adolescents. Design: A two-group, pragmatic randomized controlled trial with pretest–posttest and 3-mo follow-up assessments. Setting: A research laboratory or virtually via computer at participants' home. Participants: Thirty-six parents (individuals or couples) of autistic adolescents ages 12 to 18 yr were recruited. Intervention: The experimental group (n = 20) received the OT-Parentship intervention, and the control group (n = 16) received a psychoeducational video-based intervention. Outcomes and Measures: The study evaluated parental resilience (Autism: Parenting Questionnaire [APQ]), self-determination (Basic Psychological Need Satisfaction in Relationships [BPNSR]), and occupational performance (Canadian Occupational Performance Measure [COPM]). Adolescents' occupational performance was identified by their parents (COPM). Results: The experimental group demonstrated greater gains in outcomes compared with the control group. Significant Group × Time interactions were found for the APQ, BPNSR competence, and parent and adolescent COPM. The experimental group also showed significant improvement in BPNSR autonomy and relatedness over time. These improvements were sustained at follow-up. Conclusions and Relevance: OT-Parentship effectively enhanced parental resilience, self-determination, and parent and adolescent occupational performance, highlighting the potential of parent-centered interventions to improve family outcomes. Plain-Language Summary: Raising an adolescent with autism can bring distinct challenges for parents as they manage the specific demands and complexities that frequently arise in their daily lives. This study explored a new occupational therapy program, OT-Parentship, to help parents of autistic adolescents feel more capable and confident. OT-Parentship combines a structured approach based on integrated theoretical models to empower parents to address their needs and support their adolescent's functional independence through a collaborative process. We compared the OT-Parentship program with a program that used educational videos. Results showed that parents who participated in OT-Parentship experienced significant improvements in their parental resilience, sense of self-determination, and both their own occupational performance and that of their adolescent. These positive changes were seen both immediately after the program and three months later. Our findings highlight the importance of supporting parents of autistic adolescents and suggest that OT-Parentship may be a valuable tool for enhancing parenting abilities and supporting autistic adolescents in their everyday lives. This study explored a new occupational therapy program, OT-Parentship, to help parents of autistic adolescents feel more capable and confident.